Review: Application of Protein-Based Raw Materials in Health Foods in China - Hao Duan; Gaigai Liu; Jiaqi Liu; Zhuoye Wang; Shuyuan Bao; Xinyue Chang; Wenjie Yan (Foods)
Raw protein materials are beneficial for human health, so they are being increasingly used in health foods. In recent years, there has been more and more research on and applications of raw protein materials, but few teams have conducted a detailed review of the application status of raw protein materials in China’s health foods, the basis for their compliance and use, and the research on their health care functions. Therefore, this review evaluates the application of animal and plant proteins in China’s health foods, the impact of animal and plant proteins on human health, and future research recommendations for animal and plant proteins. This review analyzes and discusses the data on approved health foods that have been verified to contain raw protein materials (mainly including the number of protein health foods approved over the years, the classification of raw protein materials and types of relevant regulations, the analysis of the frequency of use of raw protein materials, and the functions of approved health foods). Through this process, the application of raw protein materials in health foods in China is systematically reviewed. In short, through data analysis, this study found that in 1996~2024, a total of 1142 health foods containing raw protein materials were approved in China, which are mainly divided into animal proteins, vegetable proteins, microbial proteins, and peptide raw materials, and peptide raw materials comprise the majority. The compliance applications of these ingredients are mainly related to China’s five categories of food regulations. The results show the following for health foods containing raw protein materials: in terms of the dosage form, they are mainly solid preparations; according to their functional claims, they mainly help to enhance immunity, help improve bone density, help improve skin moisture, and relieve physical fatigue; and in the application of raw materials, it is found that the use of raw materials such as casein phosphopeptide, soybean protein isolate, whey protein, collagen, spirulina, and other raw materials in products is relatively high. Finally, based on these studies, this paper discusses suggestions for raw protein materials in the future development of health food in China and also discusses the limitations of the current research in this review.